(untitled) (Pulse, 2017)
Background: Although hysteroscopy has proved to be a standard diagnostic tool in the uterine pathology, its use in the primary infertility workup is not established yet and as a therapeutic role in the management of infertility although proved, not widespread in use. I therefore aimed to review the journals to work out on diagnostic and therapeutic role of hysteroscopy in the management of infertility. Method: The literature searched was published in the English language using terms for hysteroscopy, infertility, diagnostic, therapeutic, pregnancy or conception rate, polyps, fibroids, congenital anomalies, Ashermans syndrome, adhesions and assisted reproductive techniques in MEDLINE, EMBASE, GOOGLE, SAGES, RCOG for relevant studies. Importance given to randomized controlled trial, prospective or retrospective studies with large study population. Results: I summarized and appraised the evidence for the benefit yielded by the use of hysteroscopy. It is found that as diagnostic tool in infertility workup hysteroscopy is superior to other available methods. Although there was no signifi- cant difi’erence regarding findings of intrauterine pathology between primary and secondary infertility, it is obvious that hysteroscopic removal of these pathology increased pregnancy rate not only in these two groups but also in In-vitro fertilization (IVF) and Intrauterine insemination (IUI) failure cases. Conclusion: Consideration should be given not only as a therapeutic role of hysteroscopy but also as a primary infertility workup in the management of infertility. Pulse Vol.9 January-December 2016 p.37-44